2019
DOI: 10.1002/jcp.28560
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate suppresses NOD1‐mediated inflammatory molecules expressed in bovine hepatocytes during iE‐DAP and LPS treatment

Abstract: Nucleotide oligomerization domain protein-1 (NOD1), a cytosolic pattern recognition receptor for the γ-D-glutamyl-meso-diaminopimelic acid (iE-DAP) is associated with the inflammatory diseases. Very little is known how bovine hepatocytes respond to specific ligands of NOD1 and sodium butyrate (SB). Therefore, the aim of our study was to investigate the role of bovine hepatocytes in NOD1-mediated inflammation during iE-DAP or LPS treatment or SB pretreatment. To achieve this aim, hepatocytes separated from cows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…NOD1 is widely expressed in IECs and laminar immune cells, and its expression in macrophages and IECs is important for inducing the immune response to bacteria and the production of antimicrobial peptides [ 43 ]. NOD1 can also activate the NF-κB and MAPK pathways to regulate inflammation reaction [ 44 ]. We examined the pathway of ATG16L1/NOD1/RIPK2 in IEC-18 and found that BBR can increase the expression of ATG16L1 and reduce the expression of NOD1 and RIPK2 in both RNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…NOD1 is widely expressed in IECs and laminar immune cells, and its expression in macrophages and IECs is important for inducing the immune response to bacteria and the production of antimicrobial peptides [ 43 ]. NOD1 can also activate the NF-κB and MAPK pathways to regulate inflammation reaction [ 44 ]. We examined the pathway of ATG16L1/NOD1/RIPK2 in IEC-18 and found that BBR can increase the expression of ATG16L1 and reduce the expression of NOD1 and RIPK2 in both RNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…RIPK2 is also known as RIP-like-interacting caspase-like apoptosis-regulatory protein kinase or CARD-containing IL-1b converting enzyme-associated kinase [ 1 , 23 ]. RIPK2, as a critical protein for the signaling from NOD-like receptors, always triggered MAPK, ERK2, and JNK activation and further affect apoptosis [ 24 ]. Thus, target treatment on RIPK2 showed an ideal control of inflammatory diseases, such as cystic fibrosis, asthma, inflammatory bowel disease and pancreatitis [ 3 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium butyrate could inhibit the inflammation induced by iE-DAP and LPS in bovine hepatocytes via suppressing NOD1and NOD1-mediated inflammatory molecules (IL6, IL8, TNF-α, etc.) expression in vitro [ 12 , 16 ]. Similarly, several studies have suggested that supplementation of sodium butyrate could comprehensively reduce the body injuries induced by HC diet in ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium butyrate, as a histone deacetylase (HDAC) inhibitor, facilitates gene transcription by inhibiting HDAC [ 10 , 16 ] and possesses anti-inflammatory, anti-oxidative, anti-apoptotic and other activities [ 12 ]. In addition, oral administration of sodium butyrate promotes ruminal development and improves production performance and health status in young calves [ 10 , 17 ].…”
Section: Introductionmentioning
confidence: 99%